Keynesian Without the Policy: Why the Business Cycle is all about Business Confidence and Finance - Bergström, Karl (Journal of Economic Analysis, 2023)
Many of Keynes´s ideas and concepts are proven correct in this paper. The demand side, mainly business investments, drives the economy. Business firms steer the business cycle via profit expectations and animal spirits. Injections to and withdrawals from the circular flow of income are multiplied throughout the economy in accordance with Keynes´s multiplier. A sudden and sharp rise in households´ saving rates has a detrimental effect on aggregate demand, in line with Keynes´s paradox of thrift. Finance, not saving in the S=I sense, is the necessary condition for business investments and economic growth to be realized. Keynes´s finance motive thus makes money endogenous, contradicting the textbook result that exogenous money steers aggregate demand, contradicting the mainstream loanable funds theory and putting into question the Keynesian theory of sticky prices as a condition for real growth. However, a crucial omission in Keynes´s productive writings is the lack of an accelerator tying income to investment. Some of his followers such as Paul Samuelson tried to remedy that by developing multiplier-accelerator models. The problem with them is that the accelerator lacks micro foundations, in specific disregarding business confidence. Linking macro accounting identities with empirical national accounts data for five major economies produces the finding that business firms explain more than all aggregate expenditure growth during a 25-year period. Thus, it is concluded that business confidence is the root of the business cycle. Making the accelerator account for business confidence casts new light on the perhaps most well-known Keynesian “truth”: active fiscal policy as a main force stabilizing the business cycle......